Abū ʼl-ʿAbbās al-Lawkarī (d. after 503/1109): Bayān al-ḥaqq bi-ḍamān al-ṣidq. An Early 'Reader' in Avicenna's Philosophy : Al-ʿIlm al-ṭabīʿī 1 & 2: Physics & De caelo. Editio Princeps Based on the Paris and Tehran Manuscripts, with a Brief Introduction - Esmaeili, Mohammad Javad; Lameer, Joep (Islamic Philosophy, Theology and Science. Texts and Studies, 2025)
This edition comprises the first two books of the natural philosophy section of a unique teacher's manual on Avicenna's philosophy, authored by his second-generation student Abū 'l-ʿAbbās al-Lawkarī (d. after 503/1109). Al-Lawkarī was the person responsible for promoting Avicenna's philosophy in Khorasan at a time when theologians like Abū Ḥāmid al-Ghazālī (d. 505/1111) condemned its most fundamental tenets. The importance of this work lies in al-Lawkarī's endeavour to provide the resources for a condensed yet comprehensive lecture course on Avicenna's philosophy, with the aim of perpetuating his ideas. His covert use of the work of his teacher Bahmanyār (d. 458/1066) is especially noteworthy, here as well as in other sections of this work.